1979
DOI: 10.1021/bi00583a011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lactate transport and glycolysis in Ehrlich ascites tumor cells by bioflavonoids

Abstract: Bioflavonoids are potent inhibitors of lactate transport in Ehrlich ascites tumor cells. The most effective bioflavonoids have four to five hydroxyl groups. Sugar substitution at carbon three, or reduction of the double bond between carbons two and three, decreases their inhibitory activity. Quercetin, the most extensively studied of these compounds, inhibits lactate efflux by 50% at 0.1 micrograms/mg of protein. On addition of quercetin to glycolyzing Ehrlich ascites tumor cells, lactate accumulates inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 18 publications
4
70
0
Order By: Relevance
“…Conversely, as shown in the WiDr model, the relative expression or activity of MCT1 in vitro had no prognostic value for therapeutic gain in vivo, most probably because the onset of metabolic symbiosis is under the control of microenvironmental influences. Finally, a number of reports have attributed to MCT1 a role in lactate efflux in tumor cells with active aerobic glycolysis (33,(38)(39)(40)(41). These studies showed further evidence of lethal intracellular acidification upon MCT1 inhibition in vitro.…”
Section: Figurementioning
confidence: 86%
“…Conversely, as shown in the WiDr model, the relative expression or activity of MCT1 in vitro had no prognostic value for therapeutic gain in vivo, most probably because the onset of metabolic symbiosis is under the control of microenvironmental influences. Finally, a number of reports have attributed to MCT1 a role in lactate efflux in tumor cells with active aerobic glycolysis (33,(38)(39)(40)(41). These studies showed further evidence of lethal intracellular acidification upon MCT1 inhibition in vitro.…”
Section: Figurementioning
confidence: 86%
“…All three MCT blockers that were tested reduced CAP recovery after a 60 min period of glucose withdrawal. Quercetin preferentially inhibits lactate efflux from cells (Belt et al, 1979) (see also McKenna et al, 1998). When 20 mM lactate was added to the glucose-free perfusate, quercetin had no effect on the CAP (see Fig.…”
Section: Discussionmentioning
confidence: 96%
“…We first tested the bioflavonoid quercetin, which preferentially blocks extrusion of lactate (Belt et al, 1979; Volk et al, Figure 4. Effect of nerve glycogen content on axon function during, and recovery from, a 60 min period of glucose deprivation.…”
Section: Blockade Of Lactate Transport and Axon Function During Glucomentioning
confidence: 99%
“…First, we determined the intracellular concentration of lactate, the product of the generation of ATP via the anaerobic catabolism of glucose. The intracellular accumulation of lactate can lead to the inhibition of glycolysis (28), as such heat shock could affect oxidative phosphorylation via the inhibition of glyolysis by FIGURE 4. Hyperthermia preserved association of Hsp90 and eNOS even in hyperglycemia.…”
Section: Increased Hsp90⅐enos Interactions In Heat-shocked Cells and mentioning
confidence: 99%